In vivo visualization of connections among revised Papez circuit hubs using full q-space diffusion spectrum imaging tractography. (15th August 2017) - Wei, Peng-Hu; Mao, Zhi-Qi; Cong, Fei; Yeh, Fang-Cheng; Wang, Bo; Ling, Zhi-Pei; Liang, Shu-Li; Chen, Lin; Yu, Xin-Guang
Highlights: A generally defined ventral hippocampal commissure was visualized in all datasets. The RSC and PCC may represent separate functional hubs in human. DSI may have potential use in the diagnosis of memory-related disorders. Abstract: Structural connections among the hubs of the revised Papez circuit remain to be elucidated in the human brain. As the original Papez circuit failed to explain functional imaging findings, a more detailed investigation is needed to delineate connections among the circuit's key hubs. Here we acquired diffusion spectrum imaging (DSI) from eight normal subjects and used data from the Human Connectome Project (HCP) to elucidate connections among hubs in the retrosplenial gyrus, hippocampus, mammillary bodies, and anterior thalamic nuclei. Our results show that the ventral hippocampal commissure (VHC) was visualized in all eight individual DSI datasets, as well as in the DSI and HCP group datasets, but a strictly defined VHC was only visualized in one individual dataset. Thalamic fibers were observed to connect with both the posterior cingulate cortex (PCC) and retrosplenial cortex (RSC). The RSC was mainly responsible for direct hippocampal connections, while the PCC was not. This indicates that the RSC and PCC represent separate functional hubs in humans, as also shown by previous primate axonal tracing studies and functional magnetic resonance imaging observations.